Perovskite solar cell and manufacturing method thereof

By controlling the interface between the perovskite layer and the electron transport layer in perovskite solar cells using specific additives, the photoelectric conversion efficiency is improved, addressing the current limitations and achieving high performance metrics.

JP2025043180APending Publication Date: 2025-03-28NAT INST FOR MATERIALS SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023150552
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of perovskite solar cells is currently around 16%, and further improvements are needed to enhance their performance.

Method used

The photoelectric conversion efficiency of perovskite solar cells is improved by controlling the interface between the perovskite layer and the electron transport layer using additives that focus on the type of anion and the size and type of cation, forming a surface modification layer with specific anions and cations.

Benefits of technology

This approach significantly enhances the photoelectric conversion efficiency of perovskite solar cells, achieving high short circuit current, curve factor, external quantum yield, and internal quantum yield, while maintaining stability and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043180000001_ABST
    Figure 2025043180000001_ABST
Patent Text Reader

Abstract

To provide a perovskite solar cell having high photoelectric conversion efficiency.SOLUTION: A perovskite solar cell has a modifier layer formed on the surface of a perovskite semiconductor layer, the modifier layer being made of a modifier containing an anion including one or more selected from the group consisting of PF6-, BF4-, SO42-, HPO42-, and trifluoromethanesulfonate (CF3SO3-), and an electron transport layer being formed on the modifier layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a perovskite solar cell, and more particularly to a perovskite solar cell having high photoelectric conversion efficiency and a method for manufacturing the same. [Background technology]

[0002] 2. Description of the Related Art In recent years, solar cells capable of converting solar energy into electrical energy have been attracting attention as a clean energy source to replace fossil fuels in light of global environmental issues such as global warming.

[0003] Solar cells that can efficiently convert sunlight into electricity and that are currently in practical use include monocrystalline silicon, polycrystalline silicon, amorphous silicon, and inorganic solar cells such as cadmium telluride and copper indium selenide. Issues with these inorganic solar cells include, for example, that silicon-based materials require extremely high purity, and the refining process is complicated and involves many steps, resulting in high manufacturing costs.

[0004] In response to this, perovskite solar cells have been attracting attention as a new type of solar cell that is inexpensive and highly efficient (see Patent Document 1).

[0005] Perovskite solar cells are composed of, for example, a transparent electrode layer formed on a transparent substrate, a hole transport layer, a perovskite layer, an electron transport layer, and an electrode. Alternatively, they may further include an electron blocking layer and / or a hole blocking layer. The hole transport layer and the electron transport layer transport holes and electrons, respectively, while preventing reverse transport of electrons in the hole transport layer and preventing reverse transport of holes in the electron transport layer, thereby ensuring a constant current flow.

[0006] The reason perovskite solar cells are inexpensive is that the perovskite layer is made of an organic material that can be applied by coating, and can be fabricated using a low-temperature process at around 100°C. Perovskite solar cells can be manufactured using a coating method, making them suitable for large-scale cell production, and have the excellent applicability of being able to be manufactured on flexible substrates. In addition, because they can be manufactured using low-temperature processes, they also have the excellent potential to be combined in tandem with other solar cells such as silicon solar cells.

[0007] In addition to these advantages, perovskites also possess excellent charge transport properties and long diffusion lengths for photogenerated electrons and holes before they recombine, which gives perovskite solar cells the potential to achieve high photoelectric conversion efficiencies.

[0008] However, the current photoelectric conversion efficiency of perovskite solar cells is around 16%, and further improvement in photoelectric conversion efficiency is required. As an approach to this issue, for example as disclosed in Non-Patent Documents 1-3, active research has been conducted into the control of the interface between the perovskite layer and the electron transport layer by using additives. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2017-22354 A [Patent Document 2] JP 2023-036564 A [Non-patent literature]

[0010] [Non-Patent Document 1] Nature,2019,571,245 [Non-Patent Document 2] Adv.Energy Mater.,2020,1902492 [Non-Patent Document 3] Adv.Energy Mater.,2020,1902579 Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide a perovskite solar cell having high photoelectric conversion efficiency (PCE; power conversion efficiency) and a method for manufacturing the perovskite solar cell. [Means for solving the problem]

[0012] The present inventors have conducted a detailed study of the factors that greatly affect the photoelectric conversion efficiency of perovskite solar cells, and have found that high photoelectric conversion efficiency can be obtained by controlling the interface between the perovskite layer and the electron transport layer using an additive that focuses on the type of anion and the size and type of cation.The inventors have then solved the problems related to the photoelectric conversion efficiency by the configuration shown below.

[0013] (Configuration 1) On the surface of the perovskite semiconductor layer, PF 6 - , B.F. 4 - , S.O. 4 2- , H.P.O. 4 2― and trifluoromethanesulfonate (CF 3 SO 3 - A modifying material layer is formed comprising a modifying material containing an anion including one or more selected from the group consisting of A perovskite solar cell, comprising: an electron transport layer formed on the modifier layer. (Configuration 2) 2. The perovskite solar cell according to configuration 1, wherein the modifier further comprises a cation having a radius of 0.135 nm or more and 0.513 nm or less. (Configuration 3) The cation is NH 4 + , C.H. 3 NH 3 + , guanidinium cation (Gua +3. The perovskite solar cell according to claim 2, comprising one or more selected from the group consisting of 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, and 1-butyl-2,3-dimethylimidazolium cation. (Configuration 4) 4. The perovskite solar cell according to any one of configurations 1 to 3, wherein the perovskite solar cell has a transparent electrode layer, a hole transport layer, the perovskite semiconductor layer, the electron transport layer, a hole blocking layer, and a back electrode layer. (Configuration 5) preparing a transparent substrate that transmits sunlight and has a transparent electrode formed on a first main surface; forming a hole transport layer and a perovskite layer in this order on the transparent electrode; modifying the surface of the perovskite layer with an ion deficiency modifier; After the surface modification treatment, an electron transport layer, a hole blocking layer, and a back electrode are sequentially formed; The method for producing a perovskite solar cell, wherein the ion deficiency modifier comprises the modifier according to any one of claims 1 to 3. (Configuration 6) The ion-deficiency modifier is dissolved in water at 0.05 mM (mmol L−1) using one or more solvents selected from the group consisting of 2-propanol (isopropanol), toluene, xylene, chloroform, chlorobenzene, 1,2-dichlorobenzene, and diethyl ether. -1 6. The method for producing a perovskite solar cell according to claim 5, wherein the solution contains the modifier adjusted to a concentration of 10 mM from the above. (Configuration 7) 7. The method for producing a perovskite solar cell according to configuration 5 or 6, wherein the surface modification treatment is performed by one method selected from the group consisting of a spin coating method, a dipping method, a spray coating method, and a vapor deposition method. (Configuration 8) 8. The method for producing a perovskite solar cell according to any one of Configurations 5 to 7, wherein after the surface modification treatment, a heat treatment is performed before forming the electron transport layer. (Configuration 9) The method for producing a perovskite solar cell according to configuration 8, wherein the temperature of the heat treatment is 90°C or higher and 110°C or lower. Effect of the Invention

[0014] The present invention provides a perovskite solar cell with high photoelectric conversion efficiency and a method for producing the perovskite solar cell. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram showing the structure of a perovskite solar cell of the present invention. [Diagram 2] FIG. 2 is a schematic diagram for explaining the mechanism of the effect of the present invention. [Diagram 3] FIG. 2 is a flow chart showing the manufacturing process of the solar cell of the present invention. [Figure 4] FIG. 1 is a characteristic diagram showing the cation size dependence of photoelectric conversion efficiency (PCE). [Diagram 5] FIG. 1 is a characteristic diagram showing the cation size dependence of short circuit current (JSC). [Figure 6] FIG. 1 is a characteristic diagram showing the cation size dependence of the fill factor (FF). [Figure 7] FIG. 1 is a characteristic diagram showing the cation size dependence of the external quantum yield (EQE). [Figure 8] FIG. 1 is a characteristic diagram showing the cation size dependence of the internal quantum yield (IQE). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] (Embodiment 1) In the first embodiment, a perovskite solar cell and a manufacturing method thereof of the present invention will be described.

[0017] <Structure> First, the concept of the present invention will be explained with a focus on the perovskite layer.

[0018] Perovskite in Perovskite Solar Cells is ABX3 It is represented by, and the A site is a methylammonium ion (CH 3 NH 3 + ), formamidinium ion (H 2 NCHNH 2 + ), an organic or inorganic cation such as cesium (Cs), the B site is a metal ion such as Pb 2+ or Sn 2+ and so on, and the X site consists of halide ions such as I - , Br - , Cl - and so on. The ion sizes of the A site, B site, and X site for forming the perovskite crystal structure are determined by the tolerance factor or tolerance factor (t). Let the ionic radii of the A site, B site, and X site be r A , r B , and r X respectively, then the tolerance factor (t) is represented by the following formula (1). Here, for the perovskite structure, t needs to satisfy the range of 0.81 < t < 1.1.

[0019]

Equation

[0020] In the perovskite layer responsible for the photoelectric conversion function, electrons and holes are generated with light irradiation. However, the inventor considered that due to the factors shown in the following (1) to (3), the photoelectric conversion efficiency (PCE) decreased and the inherent PCE of the perovskite could not be extracted. (1) Halide ions (I - , Br - , Cl - ) that can move in the perovskite layer move across the interface from the X site of the perovskite layer to a layer that transports charges such as the electron transport layer or the hole transport layer due to an electric field or the like. (2) Due to the energy level mismatch occurring at the interface between the perovskite layer and the electron transport layer, the movement of electrons generated by light irradiation to the electron transport layer is hindered. (3) Charge recombination occurs, in which the electrons and holes generated by light irradiation recombine through defect levels that arise at the interface between the perovskite layer and the charge transport layer.

[0021] In order to solve these problems (1) to (3), the inventors considered modifying the surface of the perovskite layer on the electron transport layer side with a modifier (ion deficiency modifier), and conducted experiments to find the optimal modification, which led to the present invention. The points to consider when conducting this search are as follows: [1] Select a modifier from among materials containing relatively large anions. The Coulomb repulsion of these anions suppresses the movement of halide ions (anions) across the interface between the perovskite and the electron transport layer, which is the issue in (1). Because the anions in the modifier itself are large, they have difficulty penetrating into the perovskite layer and tend to remain on the surface. [2] The anions of the modifier are used to negatively charge the perovskite surface, controlling the valence band edge and conduction band edge of the perovskite layer. This control ensures a smooth flow of electrons from the perovskite layer to the electron transport layer, which was the challenge in (2). [3] The perovskite surface defects caused by X-site deficiencies, etc. are passivated with a modifier, thereby suppressing charge recombination through defect levels that occur at the interface between the perovskite layer and the charge transport layer, which was the issue in (3).

[0022] As shown in FIG. 1, the perovskite solar cell 101 of the first embodiment includes a transparent substrate 11, a transparent conductive layer 12, a hole transport layer 13, an X-PACz layer (surface compensation band) 13a, a perovskite layer 14, a surface modification layer (ion deficiency modifier layer) 15, an electron transport layer 16, a hole blocking layer 17, a back electrode 18, and a metal film (wiring layer) 19. The solar cell is configured so that light 20 is irradiated from the transparent substrate 11 side. The X-PACz layer (surface compensation band) 13a is a layer introduced for the purpose of improving the photoelectric conversion efficiency, and its effect is disclosed in Patent Document 2, but it can be omitted. The hole blocking layer 17 can also be omitted depending on the material of the electron transport layer 16. The transparent electrode layer 12 is electrically connected to a first terminal electrode (not shown), and the back electrode 18 is electrically connected to a wiring layer 19 forming a second terminal electrode.

[0023] A characteristic feature of the first embodiment is that a surface modification layer (ion deficiency modifier layer) 15 is formed on the surface of the perovskite layer 14 on the electron transport layer 16 side, as shown in FIG. 6 - , B.F. 4 - , S.O. 4 2- , H.P.O. 4 2― and trifluoromethanesulfonate (CF 3 SO 3 - ) is a layer made of a material containing an anion including one or more selected from the group consisting of

[0024] The Coulomb repulsive force of these anions suppresses the movement of halide ions (anions) across the interface between the perovskite layer 14 and the electron transport layer 16, which is the problem (1) described above. In addition, the energy level mismatch occurring at the interface between the perovskite layer 14 and the electron transport layer 16, which was the problem described above in (2), is suppressed, and electrons generated by light irradiation can move more smoothly to the electron transport layer. Furthermore, the recombination of electrons and holes generated by light irradiation through defect levels occurring at the interface between the perovskite layer 14 and the charge transport layer 16, which is the problem (3) described above, is suppressed by the passivation effect. The above effects improve the photoelectric conversion efficiency of perovskite solar cells.

[0025] Next, each layer constituting the perovskite solar cell 101 of the present invention will be described.

[0026] The transparent substrate 11 is a base that transmits sunlight and has a rigidity equal to or greater than a predetermined value. Various types of glass, such as quartz glass, flint glass, and soda-lime float glass, can be preferably used, but transparent plastics, such as acrylic and polycarbonate, can also be used. Glass has the characteristics of being highly transparent (high transmittance) to sunlight, having sufficient rigidity, and excellent light resistance and weather resistance. Plastic can be easily processed into any shape and can be made flexible, making it suitable for applications in which a curved solar cell is produced or a solar cell is flexibly bent for use.

[0027] Indium tin oxide (ITO) can be used as the material for the transparent conductive layer (transparent electrode) 12. Fluorine-doped tin oxide (FTO) can also be used. From the viewpoint of improving light resistance, it is preferable to form the ITO film by a sputtering method. Specifically, RF sputtering is preferable with ITO as the target and a rare gas such as argon (Ar) gas or krypton (Kr) gas as the sputtering gas. The substrate temperature may be room temperature, but is not limited to room temperature. In addition, it is preferable to perform a heat treatment at 150°C or higher after the ITO film formation, since this improves the solar light transmittance and reduces the electrical resistance. On the other hand, a heat treatment at a temperature exceeding 300°C is not preferable because it increases the electrical resistance. ITO is highly transparent and has a relatively low electrical resistivity for a transparent conductive film. In addition, since indium (In) and tin (Sn) are oxidized and fixed, these metals are difficult to diffuse, and ITO has the interdiffusion prevention function necessary for improving light resistance. The ITO film thickness of the transparent electrode 12 is preferably 150 nm or less. On the other hand, in order to ensure the necessary conductivity, the ITO film thickness is preferably 100 nm or more. The lower the ITO film resistance, the better, and it is preferably more than 0 Ω / sq and 15 Ω / sq or less.

[0028] In order to reduce the resistance of the transparent electrode 12, a metal lead wire may be added between the ITO film and the transparent substrate 11. Examples of materials for the metal lead wire include platinum (Pt), gold (Au), silver (Ag), copper (Cu), aluminum (Al), nickel (Ni), and titanium (Ti). It is preferable to form the metal lead wire on the transparent substrate 11 by a sputtering method or a vapor deposition method, and then form the ITO film thereon. However, since providing the metal lead wire reduces the amount of incident light, it is preferable that the thickness of the metal lead wire be 0.01 mm or more and 3 mm or less.

[0029] The hole transport layer 13 is made of inorganic NiO. x Examples of suitable materials include membranes, Spiro-OMeTAD (2,2´,7,7-Tetrakis(N,N-di-p-methoxyphenylamino)-9,9´-spirofluorene), PTAA (Poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), and MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid). In particular, the hole transport layer 13 is made of inorganic NiO x When the hole transport layer 13 is made of a film, a layer having a large area with few pinholes and cracks can be formed, and the light irradiation resistance can be increased. Other methods for forming the hole transport layer 13 include a coating method and a casting method. The thickness of the hole transport layer 13 is preferably 4 nm to 50 nm, more preferably 4 nm to 18 nm. When the thickness of the hole transport layer 13 is in this range, high photoelectric conversion efficiency can be obtained. Furthermore, when the thickness of the hole transport layer 13 is 15 nm to 18 nm, high long-term reliability can be achieved. This is because pinholes in the hole transport layer 13 are suppressed.

[0030] NiO as hole transport layer 13 x When a NiO film is used, the NiO x It is also preferable to dope the film with metal ions other than Ni. Examples of metal ions include ions of alkali metals, alkaline earth metals, transition metals, etc. Specific metal ions include Li + , Na + , K + , Mg 2+ , Cu 2+ , Fe 2+ , Mn 2+ , and Zn 2+ At least one selected from the group consisting of + and Mg 2+ At least one selected from the following: + and Mg 2+ may be used simultaneously. The doping concentration is preferably from 0.5 mol % to 50 mol %, more preferably from 2 mol % to 30 mol %. These metal ions can be introduced into the hole transport layer 13 by, for example, incorporating them into the target material used for sputtering.

[0031] The X-nPACz layer 13a is a layer made of a substance represented by chemical formula (1), in which X is OR or R, O is oxygen, R is a linear hydrocarbon group having 1 to 12 carbon atoms, and n is an integer of 2 to 12. The presence of this layer results in NiO xVacancy at the interface of the film 13 and in the perovskite layer 14 is suppressed, improving the photoelectric conversion efficiency of the perovskite solar cell 101. Here, vacancy refers to the vacancy of halide ions such as iodine (I), chlorine (Cl) or bromine (Br).

[0032] n in formula (1) is more preferably 2 or 4, and X in chemical formula (1) is OCH 3 It is even more preferable that n is 2, that is, MeO-2PACz represented by chemical formula (2), since the formation of vacancy is further suppressed and the photoelectric conversion efficiency is further increased.

[0033] [ka]

[0034] In addition, X-nPACz is NiO x By applying heat treatment on top of the NiO x The temperature for this heat treatment is preferably 20° C. or higher and 150° C. or lower to promote the surface modification, and heat treatment within this temperature range can be preferably used. X-nPACz is NiO x By covering the NiO, a uniform hole transport layer is formed. In other words, X-nPACz functions as a surface compensation zone. x As long as it is not near the interface of the membrane 13 and the vacancy of the halide ions in the perovskite layer 14, there will be no adverse effects.

[0035] The material constituting the perovskite layer 14 is not particularly limited, and may be CH 3 NH 3 PbI 3 , CH(NH 2 ) 2 PbI 3 , CsPbI 3 , C.H. 3 NH 3 SnI 3 , C.H. 3 NH 3 Snx Pb (1-x) I 3 , CH(NH 2 ) 2 SnI 3 , F.A. 0.84 Cs 0.12 Rb 0.04 PbI 3 and the like, preferably CH 3 NH 3 PbI 3 , CH(NH 2 ) 2 PbI 3 , and F.A. 0.84 Cs 0.12 Rb 0.04 PbI 3 The following can be mentioned. Furthermore, materials in which some of the iodine (I) in these materials has been replaced with chlorine (Cl), such as CH 3 NH 3 PbI 3―x Cl x This is more preferable because it improves the photoelectric conversion efficiency and light irradiation resistance and reduces deterioration over time when left unattended. Here, the reaction for replacing a part of iodine with chlorine can be a chlorine-mediated interdiffusion method.

[0036] The perovskite layer 14 may be a single layer film or a laminated film made up of multiple layers. A single-layer film has the advantage that it requires fewer manufacturing steps, is suitable for mass production as a solar cell, and allows for cost reduction. On the other hand, in the case of a laminated film, multiple perovskites with different light absorption bands are laminated to form a tandem structure, which has the advantage that it is possible to efficiently absorb light in a wide wavelength range and increase the photoelectric conversion efficiency of the entire solar cell. a Cs b Rb 1-a-b Pb(I x Br 1-x ) 3 (FA=(I x Br 1-x ) 3(FA = formamidinium (H 2 NCHNH 2 ), 0 < a ≤ 1, 0 < b ≤ 1, 0 < x ≤ 1), a structure in which a perovskite is laminated on a Sn-based perovskite having a narrow bandgap can be mentioned.

[0037] The perovskite layer 14 can be formed by a coating method such as spin coating. For example, a perovskite precursor dissolved in a solvent is prepared, and after spin coating, heat treatment is applied to form the perovskite layer 14. As a specific example of the formation of the perovskite layer 14, CH 3 NH 3 PbI 3 is mentioned. When preparing a perovskite precursor solution in which methylammonium iodide CH 3 NH 3 I (abbreviated as "MAI") and lead iodide PbI 2 are dissolved in a solvent, and spin coat it. As the solvent, for example, dimethyl sulfoxide (DMSO) can be used. At the time of spin coating, it is preferable to drop a small amount of toluene or the like as a volatile preparation for the purpose of reducing striation and film thickness uniformity. The heat treatment temperature is preferably 50 ° C or higher and 120 ° C or lower.

[0038] The surface modification layer (ion deficiency modifier layer) 15 is a surface modification layer made of a modifier containing one or more anions selected from the group consisting of PF 6 - , BF 4 - , SO 4 2- , HPO 4 2― and trifluoromethanesulfonate (CF 3 SO 3 - ). Furthermore, the ion deficiency modifier layer 15 more preferably contains a cation having a size of 0.135 nm or more and 0.513 nm or less in radius. Specific examples of the cation include NH 4 + , CH 3 NH3 + , guanidinium cation (Gua + ), 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, and 1-butyl-2,3-dimethylimidazolium cation. + The structures of the 1-methylimidazolium cation, the 1-ethyl-3-methylimidazolium cation, and the 1-butyl-2,3-dimethylimidazolium cation are shown in chemical formulas (3), (4), (5), and (6), respectively.

[0039] [ka]

[0040] By including the above-mentioned cations in the ion deficiency modifier layer 15, a perovskite solar cell 101 that can obtain a stable and high photoelectric conversion efficiency is provided.

[0041] The material constituting the electron transport layer 16 is not particularly limited, but for example, an n-type conductive polymer, an n-type low molecular weight organic semiconductor, a graphene material, and an n-type metal oxide can be used. 61 Poly(butyl methyl ester) (PCBM) can be formed by a coating method, and is preferably used as the electron transport layer 16 from the viewpoints of throughput and production costs.

[0042] The hole blocking layer 17 may be an oxide film doped with metal ions, such as at least one selected from zinc oxide, titanium oxide, and tin oxide. The doped metal ions may be, for example, W 6+ , Nb 5+ , Sb 5+ , Ta 5+ , Al 3+ , Y 3+ , Ga 3+The doping concentration is 0.5 mol % or more and 50 mol % or less, preferably 0.5 mol % or more and 20 mol % or less. For example, a zinc oxide film (AZO) doped with 1.6 mol % aluminum can be preferably used as the hole blocking layer 17. The thickness of the hole blocking layer 17 is preferably 30 nm or more and 150 nm or less, and more preferably 40 nm or more and 100 nm or less, taking into consideration the electrical resistance and the uniformity of the layer thickness.

[0043] The back electrode 18 is a metal film such as silver or a composite film of indium tin oxide (ITO) and a metal such as silver. This film is preferably formed by a sputtering method. When ITO is also used, it is possible to increase the back light reflectance by utilizing the ITO as an optical interference film and increase the photoelectric conversion efficiency of the solar cell as a whole. The method for forming ITO is preferably RF sputtering using ITO as a target and a rare gas such as argon (Ar) gas or krypton (Kr) gas as a sputtering gas. The substrate temperature may be room temperature, but is not limited to room temperature. In addition, it is effective to perform a heat treatment after the ITO film formation, but in order not to damage the perovskite layer 4, etc., the heat treatment should be performed at 140°C or less, preferably 120°C or less. Examples of the material for the wiring 19 include metals such as silver, aluminum (Al), tungsten (W), copper (Cu), and gold (Au), and alloys such as Al-Si. The wiring 19 may be produced in the form of an extraction line of the back electrode 18 by utilizing the back electrode 18.

[0044] The perovskite solar cell 101 having the structure of the first embodiment solves the above problems (1) to (3) and provides a perovskite solar cell with high photoelectric conversion efficiency.

[0045] <Manufacturing method> The method for manufacturing the perovskite solar cell 101 will now be described with reference to FIG. 3, which shows a flow chart of the manufacturing steps. The perovskite solar cell 101 is manufactured by sequentially carrying out the steps of forming a transparent conductive layer 12 made of ITO on a transparent substrate 11 (S11), forming a hole transport layer 13 (S12), forming a surface compensation zone 13a made of an X-nPACz layer (S12a), forming a perovskite layer 14 (S13), forming an ion deficiency modification layer 15 (S14), forming an electron transport layer 16 (S15), forming a hole blocking layer 17 (S16), forming a back electrode 18 (S17), and forming wiring (S18). Here, step S12 can be omitted, and step S16 can also be omitted depending on the material of the electron transport layer 16.

[0046] The hole transport layer 13 includes Spiro-OMeTAD (2,2´,7,7-Tetrakis(N,N-di-p-methoxyphenylamino)-9,9´-spirofluorene), PTTA(Poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), MeO-2PACz and nickel oxide film (NiO x The method of formation includes coating, casting, and PVD methods such as sputtering. Among these, inorganic nickel oxide films (NiO x ) is suitable for the hole transport layer 13 in order to obtain high photoelectric conversion efficiency. Here, the sputtering method is preferred among the PVD methods because it is suitable for mass production and has high manufacturing stability. In view of its productivity, the method of forming the hole transport layer 13 by using NiO as a target with an RF magnetron sputtering device is preferred, but a method of using Ni as a target and sputtering in the presence of oxygen can also be used. The thickness of the hole transport layer 13 is preferably 4 nm or more and 50 nm or less, and more preferably 10 nm or more and 50 nm or less, taking into consideration the electrical resistance and the thickness uniformity of the layer.

[0047] The surface compensation layer (X-nPACz layer) 13a is a layer made of a material represented by the above formula (1). In formula (1), X is OR or R, O is oxygen, R is a straight-chain hydrocarbon group having 1 to 12 carbon atoms, and n is an integer of 2 to 12. n in formula (1) is more preferably 2 or 4, and X in formula (1) is preferably OCH 3 It is even more preferred that n is 2, i.e., MeO-2PACz as shown in formula (2). The method for forming the surface compensation zone 13a may be one selected from the group consisting of spin coating, dipping, spray coating, and vapor deposition. Among these, the spin coating and dipping methods, which have few defects and are suitable for mass production, are preferably used. X-nPACz is NiO x After the formation of the layer on the substrate, it is preferable to perform a heat treatment at a temperature of 20° C. to 150° C. This treatment allows the X-nPACz to act as a surface compensation zone, and the hole transport layer becomes dense and has high in-plane uniformity.

[0048] From the viewpoints of mass productivity and defect reduction, it is preferable to form the perovskite layer 14 by a coating method, and a chlorine-containing perovskite is preferable for the perovskite layer 14. In addition, from the viewpoints of ensuring long-term stability as a solar cell and improving photoelectric conversion efficiency, it is preferable to subject the layer to a heat treatment at 60° C. or more and 150° C. or less after coating formation.

[0049] The ion deficiency modifier layer 15 is formed by applying a solution containing the ion deficiency modifier to the surface of the perovskite layer 14 by a spin coating method, a dipping method or a spray coating method, or by a vapor deposition method. Here, the ion deficiency modifier is PF 6 - , B.F. 4 - , S.O. 4 2- , H.P.O. 4 2― and trifluoromethanesulfonate (CF 3 SO 3 -) is dissolved in 0.05 mM (mmol L−1) of 2-propanol (isopropanol), toluene, xylene, chloroform, chlorobenzene, 1,2-dichlorobenzene, and diethyl ether. -1 ) to a concentration of 10 mM.

[0050] The ion deficiency modifier preferably further contains a cation having a radius of 0.135 nm or more and 0.513 nm or less. Specific examples of the cation include NH 4 + , C.H. 3 NH 3 + , guanidinium cation (Gua + ), 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, and 1-butyl-2,3-dimethylimidazolium cation. Here, the ratio of anion and cation to be charged in the ion deficiency modifier is 1:1. After forming the ion deficiency modifier layer 15, it is preferable to perform a heat treatment before forming the electron transport layer 16. The temperature of the heat treatment can be 90° C. or higher and 110° C. or lower. This heat treatment has the effect of fixing the ion deficiency modifier in the perovskite crystal, on the surface, and at the grain boundaries.

[0051] The electron transport layer 16 may be a PCBM film or a fullerene C 60 Membrane, or PCBM membrane and C 60 These films can be formed by coating methods, vacuum deposition methods, etc. The hole blocking layer 17 is preferably made of an aluminum zinc oxide film (AZO), a LiF film, or a bathocuproine (BCP) film. These films can be formed by a coating method, a vacuum deposition method, or the like.

[0052] Examples of the back electrode 18 include a single layer film made of a metal such as Ag or an alloy such as Al-Si, and a laminate film of ITO and a metal or alloy. Methods for forming these films include a sputtering method, a vapor deposition method, a CVD method, and a coating method. Examples of the wiring 19 include a single layer film made of a metal such as Al, W, or Cu, an alloy such as Poly-Si or Al-Si, and a laminated film with a metal or an alloy. Methods for forming these films include a sputtering method, a vapor deposition method, a CVD method, and a coating method.

[0053] When a perovskite solar cell is manufactured in the manner described above, the solar cell 101 becomes a solar cell with high photoelectric conversion efficiency. EXAMPLES

[0054] Example 1 The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0055] 1. Solar Cell Fabrication 1-1. Preparation of a transparent substrate with a transparent electrode layer A transparent substrate 11 was prepared, which had on its first main surface a transparent electrode layer 12 made of an ITO film patterned into a commercially available transparent electrode. The ITO film had a thickness of 150 nm and a film resistance of about 15 Ω / sq.

[0056] 1-2. Formation of hole transport layer On top of the ITO film, NiO was used as a hole transport layer 13. x The film was formed to a thickness of 20 nm by sputtering. An RF magnetron sputtering device (SVC-700 RF IN, manufactured by Sanyu Electronics Co., Ltd.) was used for this film formation. The target was 99.9% pure NiO (manufactured by Kojundo Chemical Laboratory Co., Ltd.). The sputtering gas was argon (Ar) gas, and the degree of vacuum in the sputtering chamber was 2×10 -3After the pressure was reduced to less than Pa, argon gas was introduced into the chamber at a flow rate of 20 sccm, and sputtering was performed at room temperature with a power of 50 W. The argon gas pressure at this time was 3.5 Pa. Immediately before this sputtering, the transparent substrate 1 on which the ITO film 2 was deposited was subjected to UV ozone cleaning for 20 minutes.

[0057] 1-3. Formation of surface compensation zone In a glove box filled with nitrogen, 6 mg of MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid) was dissolved in 18 mL of ethanol and filtered with a 0.22 μm syringe filter to obtain a MeO-2PACz solution. This solution was dropped onto NiOx and spin-coated at 300 rpm for 30 seconds, and then heat-treated on a hot plate at 100°C for 10 minutes to form a surface compensation zone 13a made of MeO-2PACz.

[0058] 1-4. Formation of perovskite layer (two-step method) Next, lead halide perovskite (FA) is deposited on the surface compensation zone 13a. 0.84 Cs 0.12 Rb 0.04 PbI 3 A perovskite layer 14 made of ZnO was formed to a thickness of 500 nm by a coating method.

[0059] Specifically, 9 mg of 5-AVAl, 1383 mg of PbI in DMF-DMDO consisting of 2.4 mL of DMF and 0.6 mL of DMSO were 2 (Kanto Chemical, purity 98%), 433.4 mg of formamidinium (FA´) iodide salt (FAI), 93.6 mg of CsI, and 25.5 mg of RbI were prepared and spin-coated onto the NiOx film 13 with a surface compensation band. After annealing at 105°C for 30 minutes, 0.5-10 mol% / mL of 5F-PHZ in 2-propanol (IPA) solvent was spin-coated to passivate the perovskite layer 14. The perovskite layer 14 was formed through the above process.

[0060] 1-5. Formation of ion deficiency modifier layer (perovskite surface treatment with additives) Methylammonium hexafluorophosphate (CH 3 NH 3 PF 6 ) or other additives shown in Table 1 were dissolved in 6 mL of IPA solvent, and the resulting solution was dropped onto the perovskite layer 14, followed by spin coating at 5000 rpm for 50 seconds and annealing at 100°C for 5 to 10 minutes to form the ion deficiency modifier layer 15. Here, Table 1 shows samples 1 to 12, a1 to a5 are comparative examples, and b1 and b2 are reference examples.

[0061] [Table 1]

[0062] 1-6. Formation of electron transport layer An electron transport layer 16 made of PCBM was prepared by the following procedure. A solution of 99% purity PCBM (SIGMA-ALDRICH) dissolved in anhydrous chlorobenzene at a ratio of 2% by weight was dropped onto the perovskite layer 14, and then spin-coated at 700 rpm for 7 seconds and then at 3000 rpm for 30 seconds. Heat treatment was then performed at 105°C for 15 minutes to form an electron transport layer 16 with a thickness of 50 nm.

[0063] 1-7. Formation of hole blocking layer Nanograde N-21X (Nanograde Corporation), an ink containing suspended zinc oxide nanoparticles (AZO nanoparticles) containing AvantamaAG (doped with aluminum), was dropped, and then spin-coated at 1500 rpm for 5.5 seconds and then at 4000 rpm for 20 seconds to produce a hole-blocking layer 17 made of an AZO film with a thickness of 100 nm. After applying the ink, the layer was heat-treated at 105°C for 10 minutes.

[0064] 1-8. Formation of rear electrode A back electrode 18 was formed by depositing silver (Ag) to a thickness of 150 nm by thermal evaporation.

[0065] 1-9.Sealing A cover glass was placed on the obtained cell, and the cell was sealed (not shown) using UVRESIN XNR5516Z (manufactured by NagaseChemteX), which is an ultraviolet-curable resin, to encapsulate the cell and evaluate its electrical characteristics.

[0066] 2. Photoelectric conversion characteristic evaluation The JV characteristics, external quantum yield (EQE) characteristics, and internal quantum yield (IQE) characteristics of the perovskite solar cell 101 fabricated by the above-mentioned fabrication method were investigated. The measurements were performed under the conditions of the 1-SUN standard using an AM1.5G spectrum filter, and the EQE and IQE characteristics were measured using an SM-250IQE (manufactured by Bunkoukeiki). sc ), open circuit voltage (V oc ), fill factor (FF), series resistance (R s ), parallel resistance (R sh ) and conversion efficiency (η) were calculated. The values ​​shown are the maximum values ​​obtained from data obtained using at least eight perovskite solar cells.

[0067] Table 2 shows the results of measuring the PCE for samples 1 to 12, Comparative Examples a0 to a5, and Reference Examples b1 and b2 shown in Table 1. Comparative Example a0 shows the case where the ion deficiency modifier layer 15 was not formed. Table 2 also lists the calculated anion size and the cations used. The anion size was calculated using density functional theory and was defined as half the maximum length (radius) from the molecular end to the end.

[0068] [Table 2]

[0069] As can be seen from Table 2, the surface of the perovskite semiconductor layer 14 was coated with PF 6 - , B.F. 4 - , S.O. 4 2- , H.P.O. 42― and CF 3 SO 3 - When the ion deficiency modifier layer 15, which is a layer containing anions consisting of I, was formed, a PCE exceeding 16.9% was obtained. On the other hand, in the case of the comparative example a0 in which the ion deficiency modifier layer 15 was not formed, the PCE was a low value of 16.52%. In addition, when the anion of the ion deficiency modifier layer 15 was I, - (Comparative example a1), FeCl 4 - (Comparative example a2), C(NC) 3 - (Comparative example a3), OCN - (Comparative example a4), CH 3 COO - When (Comparative Example a5) was used, the PCE was also low, at 10.43%, 4.46%, 13.85%, 16.25% and 16.35%, respectively. From the above, it is considered that the surface of the perovskite semiconductor layer 14 is formed with PF 6 - , B.F. 4 - , S.O. 4 2- , H.P.O. 4 2― and CF 3 SO 3 - The effect was confirmed when the ion deficiency modifying layer 15, which is a layer containing anions consisting of the above, was formed.

[0070] Next, the photoelectric characteristics of the perovskite solar cell 101 with respect to the size of the cations forming the ion deficiency modifier layer 15 were compared by changing the anions of the ion deficiency modifier layer 15 to PF 6 - The cation size was calculated by the maximum length from one end of the cation molecule to the other end, similar to the anion size. The cation used was NH 4 + (Sample 3), CH 3 NH 3 +The eight types are: (Sample 4), 1-methylimidazolium cation (Sample 5), 5-azoniaspiro[4,4]nonane cation (Sample 6), 1-ethyl-3-methylimidazolium cation (Sample 7), 1-butyl-2,3-dimethylimidazolium cation (Sample 8), and, as reference examples, 1-butyl-3-methylimidazolium hexafluorophosphate (Sample b1) and 1-hexyl-3-methylimidazolium hexafluorophosphate (Sample b2).

[0071] Photoelectric conversion efficiency (PCE), short circuit current (J sc The cation size dependences of the fill factor (FF) and the cation size dependences are shown in Figures 4, 5, and 6, respectively. The PCE is high, at 16% or more, when the cation size is between 0.135 nm and 0.513 nm, but when the cation size exceeds 0.513 nm, the PCE drops sharply. sc ) and the fill factor (FF) maintain high values ​​when the cation size is between 0.135 nm and 0.513 nm, but drop sharply when the cation size exceeds 0.513 nm. Furthermore, the measurement results of the external quantum yield (EQE) and internal quantum yield (IQE) are shown in Figures 7 and 8, respectively, and it can be seen that when the cation size is 0.531 nm and 0.590 nm, both the EQE and IQE decrease significantly. Note that the numbers in parentheses in the figures indicate the cation size (unit: nm). From the above, it was confirmed that the photoelectric characteristics of the perovskite solar cell 101 are improved when the ion deficiency modifier layer 15 formed on the surface of the perovskite semiconductor layer 14 contains cations with a radius of 0.135 nm or more and 0.513 nm or less. [Industrial Applicability]

[0072] INDUSTRIAL APPLICABILITY The present invention provides a perovskite solar cell with high photoelectric conversion efficiency and a method for manufacturing the perovskite solar cell, and is expected to greatly contribute to the development of industry. [Explanation of symbols]

[0073] 11 Transparent substrate (transparent support) 12 Transparent conductive layer (ITO film) 13 Hole transport layer (NiO x film) 13a Surface compensation zone, X-nPACz layer 14 Perovskite layer 15 Modifier layer (ion deficiency modifier layer) 16 Electron transport layer (PCBM film) 17 Hole blocking layer (AZO film) 18 Back electrode (ITO film, metal film) 19 Wiring 20 light 101 Perovskite solar cells

Claims

1. PF on the surface of the perovskite semiconductor layer 6 - , B.F. 4 - , S.O. 4 2- , H.P.O. 4 2― and trifluoromethanesulfonate (CF 3 SO 3 - a modifying material layer made of a modifying material containing an anion including one or more selected from the group consisting of A perovskite solar cell, comprising: an electron transport layer formed on the modifier layer.

2. The perovskite solar cell according to claim 1 , wherein the modifier further contains a cation having a radius of 0.135 nm or more and 0.513 nm or less.

3. The cation is NH 4 + , C.H. 3 N.H. 3 + , guanidinium cation (Gua + 3. The perovskite solar cell according to claim 2, comprising at least one selected from the group consisting of 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, and 1-butyl-2,3-dimethylimidazolium cation.

4. The perovskite solar cell according to claim 1 , wherein the perovskite solar cell has a transparent electrode layer, a hole transport layer, the perovskite semiconductor layer, the electron transport layer, a hole blocking layer and a back electrode layer.

5. preparing a transparent substrate that transmits sunlight and has a transparent electrode formed on a first main surface thereof; forming a hole transport layer and a perovskite layer in this order on the transparent electrode; modifying the surface of the perovskite layer with an ion deficiency modifier; After the surface modification treatment, an electron transport layer, a hole blocking layer, and a back electrode are sequentially formed; A method for producing a perovskite solar cell, wherein the ion deficiency modifier comprises the modifier according to claim 1 .

6. The ion deficiency modifier is dissolved in water at a concentration of 0.05 mM (mmol L) using one or more solvents selected from the group consisting of 2-propanol (isopropanol), toluene, xylene, chloroform, chlorobenzene, 1,2-dichlorobenzene, and diethyl ether. -1 6. The method for producing a perovskite solar cell according to claim 5, wherein the solution contains the modifier adjusted to a concentration of 10 mM from

7. 7. The method for producing a perovskite solar cell according to claim 5 or 6, wherein the surface modification treatment is performed by one method selected from the group consisting of a spin coating method, a dipping method, a spray coating method, and a vapor deposition method.

8. The method for producing a perovskite solar cell according to claim 5 , wherein a heat treatment is performed after the surface modification treatment and before the electron transport layer is formed.

9. The method for producing a perovskite solar cell according to claim 8, wherein the temperature of the heat treatment is 90°C or higher and 110°C or lower.

Citation Information

Patent Citations

  • Perovskite solar battery

    JP2017022354A

  • Perovskite solar cell, manufacturing method thereof, nickel oxide film with reduced defects at interface, and interface treatment method for nickel oxide film

    JP2023036564A